Optimality of the Friedman rule in an overlapping generations model with spatial separation - Joseph H. Haslag; Antoine Martin (Federal Reserve Bank of New York, 2005)
We examine models with spatial separation and limited communication that have shown some promise toward resolving the disparity between theory and practice concerning optimal monetary policy; these models suggest that the Friedman rule may not be optimal. We show that intergenerational transfers play a key role in this result, the Friedman rule is a necessary condition for an efficient allocation in equilibrium, and the Friedman rule is chosen whenever agents can implement mutually beneficial arrangements. We conclude that in order for these models to resolve the aforementioned disparity, they must answer the following question: Where do the frictions that prevent agents from implementing mutually beneficial arrangements come from?
Keywords: E52; E58; H21; 330; Friedman rule; overlapping generations; spatial separation; Geldpolitik; Geldmengensteuerung; Overlapping Generations; Wohlfahrtsanalyse; Privater Transfer; Theorie